Effect of CVD Process Temperature on Activation Energy and Structural Growth of MWCNTs - Shukrullah, S. (Springer Boston, 2016)
This study investigated the effect of process temperature and activation energy on chemical vapor deposition growth of multi-walled carbon nanotubes (MWCNTs). A vertically fluidized bed reactor was used to grow MWCNTs by catalytic decomposition of ethylene over Fe2O3/Al2O3 at the cost of very low activation energy of 19.516Â kJ/mole. FESEM, TEM, and Raman spectroscopy were used to characterize the growth parameters of MWCNTs in the temperature range of 873.15Â K to 1273.15 K (600Â Â°C to 1000Â Â°C). SAED patterns were taken to investigate the crystallinity of the grown structures. The experimental results revealed that MWCNTs grown at the optimum process temperature of 1073.15Â K (800Â Â°C) exhibited hexagonal crystal structures, narrow diameter distribution and shorter inter-layer spacing. However, the inner and outer walls of most of MWCNTs grown at the temperatures above and below the optimum were non-uniform and defective. The higher process temperatures promoted the agglomeration of the catalyst particles and decomposition of the carbon precursor, which in return increased the tube diameter, surface defects and amorphous carbon content in the product. The intensity ratio plots also predicted low crystallinity in MWCNTs grown at unoptimized process temperatures. The highest IG/ID ratio of 1.43 was determined at 1073.15 K (800Â Â°C), which reflects high pct yield, purity and crystalline growth of MWCNTs. Â© 2016, The Minerals, Metals & Materials Society and ASM International.